2021
DOI: 10.1155/2021/6525079
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Robust Regression Techniques: An Econometric Approach

Abstract: Consistent estimation techniques need to be implemented to obtain robust empirical outcomes which help policymakers formulating public policies. Therefore, we implement the least squares (LS) and the high breakdown robust least trimmed squares (LTS) regression techniques, while using econometric regression model based on a growth equation for the two countries, namely, India and Pakistan. We used secondary annual time series data which covers a long period of 41 years. The adequacy of the time series econometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In order to more accurately calculate the contribution of human capital to economic growth in a certain region in western country, based on Solow's total production function method, an economic growth model is constructed [26][27][28][29]. In order to establish a model that can further reflect the impact of human capital on economic growth, on the basis of the Cobb-Douglas production function model on the relationship between output and input labor and capital, taking into account the production function of human capital, the level of human capital is introduced to establish a relationship between human capital in a certain region and economic growth.…”
Section: Model Establishmentmentioning
confidence: 99%
“…In order to more accurately calculate the contribution of human capital to economic growth in a certain region in western country, based on Solow's total production function method, an economic growth model is constructed [26][27][28][29]. In order to establish a model that can further reflect the impact of human capital on economic growth, on the basis of the Cobb-Douglas production function model on the relationship between output and input labor and capital, taking into account the production function of human capital, the level of human capital is introduced to establish a relationship between human capital in a certain region and economic growth.…”
Section: Model Establishmentmentioning
confidence: 99%
“…Coefficients are then estimated by using panel robust least squares. Robust least square is applied to obtain reliable estimates as it overcomes the issue of influential observations and outliers [20]. Robust least square is preferred over ordinary least square as it can be applied with less restricted assumptions.…”
Section: Estimation Methodsmentioning
confidence: 99%
“…The experimental data from the pooled sample was fitted to three (3) regression models (table 1) using nonlinear robust regression with least absolute residuals (LAR) using the cftool in MATLAB 2022b. Robust regression was adopted as it overcomes the effect of outliers and influential observations in the data while minimizing their impact on the regression coefficients (Khan et al, 2021). Curve fitting was adopted for this study as it is the most reported method for developing moisture content based engineering property relationships in the literature.…”
Section: Simple Regression Analysis and Prediction Of Engineering Pro...mentioning
confidence: 99%